An analysis of the pragmatic functions of idiomatic expressions - Elshamy, Hala Mohamed (AUC Knowledge Fountain, 2016)

(untitled)
The purpose of the study is to investigate the idiomatic expressions and their pragmatic functions in the conversations of the novel Taxi in the light of Speech Act Theory. The study adopts a qualitative linguistic analysis method of research. After analyzing the 58 episodes of the novel ’Taxi’, the study reveals 80 idiomatic expressions fulfilling 13 pragmatic functions: describing with six subcategories, complaining, stating, concluding, and swearing, thanking, condoling, sympathizing, deploring and excusing, agreeing and opposing and advising. These pragmatic functions have been classified based on four of Searle’s speech acts: (1) representatives, (2) expressives, (3) commissives and (4) directives. Hence, the study shows that idiomatic expressions fulfill a satisfying number of pragmatic functions which in turn operate in facilitating conversations among speakers as they are stored in their memory and easily retrieved in diverse contexts. In addition, the study shows the high usage of negative pragmatic functions such as complaining, deploring, describing negative issues in comparison with positive ones in the conversations of taxi drivers. It has been also observed that these positive and negative functions shed light on a multitude of cultural aspects in Egyptian society. The study suggests pedagogical implication: the result that the idiomatic expressions perform various pragmatic functions and fulfill cultural aspects provides a rationale for including them in Arabic foreign language classes as their main aim is to use the language appropriately and achieve cultural competence as well.